Unequal growth: How household incomes and poverty in urban China have developed since 1988, with an emphasis on the period from 2007 to 2013 - Björn Gustafsson; Sai Ding (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2017)
This chapter investigates how household income, income inequality, and poverty among urban residents in China have developed since 1988, with an emphasis on the period from 2007 to 2013. We use data from the China Household Income Project (CHIP) to show that during a period when many countries in the West were experiencing stagnating or falling incomes, household incomes in urban China were growing by an average of 7 percent per annum. However, unlike during previous periods, earnings were growing by not more than 3 percent per annum, but pensions and imputed rents of owner-occupied housing were growing more rapidly. The trend whereby fewer persons in urban China have incomes that are lower than the poverty line, expressed as the constant purchasing power, continued between 2007 and 2013. We also show that income growth from 2007 to 2013 was slower in the lower part of the income distribution and thus the trend of increased income inequality in urban China continued. This also applied to the number of people falling below the relative poverty line.
Keywords: D31; O15; P25; 330; China; income; income distribution; poverty